Studi Komparatif Metode Hafalan dan Pemahaman dalam Pengajaran Al-Qur’an di MIS Nurul Yaqin NW Sabelendang - Susilawati, Seni; Sumiati; Sanudin (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2024)
This study aims to comparatively analyze the effectiveness of memorization and comprehension methods in Quranic education at MIS Nurul Yaqin NW Sabelendang, Desa Keru, Narmada, Lombok Barat. The memorization method is commonly used to enhance students' ability to accurately recall Quranic verses, while the comprehension method focuses on instilling meaning and applying the teachings of the Quran. The study employs a qualitative approach with techniques of observation, interviews, and documentation involving teachers and students from grades IV to VI. The findings indicate that the memorization method is effective in helping students master the recitation in a fluent and systematic manner, but it is less effective in fostering deep understanding. In contrast, the comprehension method encourages greater emotional and cognitive engagement, although not all students are able to memorize the text effectively. The conclusion of this study is that integrating both memorization and comprehension methods in a balanced approach provides more comprehensive results in Quranic education, addressing both memorization and meaningful interpretation. Therefore, the integration of these two methods is a strategic approach that can be applied in the curriculum of Madrasah Ibtidaiyah.